Answer:
[tex]653[/tex]
Step-by-step explanation:
we know that
the difference between [tex]900[/tex] and [tex]247[/tex] is equal to subtract [tex]247[/tex] from [tex]900[/tex]
so
[tex]900-247[/tex]
remember that
[tex]247=200+40+5+2[/tex]
substitute in the expression above
[tex]900-247=900-(200+40+5+2)[/tex]
[tex]=900-200-40-5-2[/tex] ------> [tex]=(900-200)-40-5-2[/tex]
[tex]=700-40-5-2[/tex] -----> [tex]=(700-40)-5-2[/tex]
[tex]=660-5-2[/tex] -----> [tex]=(660-5)-2[/tex]
[tex]=655-2[/tex]
[tex]=653[/tex]